Quercetin regulates phenotypic transformation of vascular smooth muscle cells induced by angiotensin Ⅱ through Nrf2/HO-1 signaling pathway - Mamatimin ABDURESHIT; Wei ZHU (Zhongguo Linchuang Yixue)
ObjectiveTo investigate the protective effect and mechanism of quercetin (QR) against angiotensin Ⅱ (Ang Ⅱ)-induced injury and phenotypic transformation in vascular smooth muscle cells (VSMCs). MethodsVSMCs were treated with Ang Ⅱ and divided into four groups: control (Ctrl), QR control, model (Ang Ⅱ), and treatment (Ang Ⅱ＋QR) groups. Intracellular reactive oxygen species (ROS) level and superoxide dismutase (SOD) activity were measured. Western blotting was used to assess protein expression related to inflammation, apoptosis, extracellular matrix (ECM) remodeling, phenotypic transformation, and the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to quantify mRNA levels of inflammatory cytokines (interleukin [IL]-1β, IL-6, and tumor necrosis factor-α [TNF-α]). Cell migration was evaluated using a scratch assay. A rescue experiment employing the Nrf2 transcriptional activity inhibitor ML385 was conducted to further validate protective mechanism of QR for VSMCs. ResultsCompared to the Ctrl group, Ang Ⅱ-treated VSMCs exhibited significantly higher ROS levels, suppressed SOD activity, upregulated expression of inflammatory proteins and mRNA (IL-1β, IL-6, TNF-α), increased matrix metalloproteinase (MMP) protein expression (P＜0.05), enhanced migration capacity, reduced expression of contractile phenotype markers (smooth muscle 22 alpha [SM22α] and α-smooth muscle actin [α-SMA]), upregulated expression of the synthetic phenotype marker osteopontin (OPN), and significantly increased apoptosis (P＜0.05). QR intervention significantly reduced intracellular ROS level, increased SOD activity, decreased protein expression of vascular cell adhesion molecule-1 (VCAM-1) and phosphorylated nuclear factor-κB (NF-κB), downregulated inflammatory cytokine transcription, upregulated contractile phenotype marker expression, and attenuated apoptosis and migration capacity (P＜0.05). The rescue experiment confirmed that QR alleviated Ang Ⅱ-induced oxidative stress, inflammation-related injury, and suppressed the transition of VSMCs towards a synthetic phenotype via activation of Nrf2. Conclusions QR mitigates Ang Ⅱ-induced oxidative stress, inflammation, and apoptosis in VSMCs, inhibits ECM remodeling and VSMCs migration, and consequently suppresses VSMCs phenotypic transformation, primarily through promoting Nrf2 expression.